Integrity of Educational Technology in Curriculum 2013: Challenges and Opportunities for Improving Learning Quality - Siregar, Nurliani; Badrudin, Rudy; Wachidah, Nor Rochmatul; Firayani, Firayani (PT. Anagata Sembagi Education, 2025)
This research endeavours to explore the complexities and prospects associated with the incorporation of educational technology into the 2013 Curriculum, aiming to elevate the standard of learning outcomes. Adopting a Systematic Literature Review (SLR) framework guided by PRISMA protocols, the study systematically examines a wide array of scholarly works to gain insights into the evolution, constraints, and strategic applications of technology within the educational landscape. The analytical procedure encompasses the formulation of key research inquiries, the establishment of stringent inclusion and exclusion benchmarks, comprehensive literature retrieval from databases such as Google Scholar, Scopus, and JSTOR, meticulous article screening, data coding, and the synthesis of core findings. From an initial pool of 229 publications, a mere 21 articles satisfied the rigorous inclusion criteria after an exhaustive selection process. The analysis underscores several critical obstacles in the realm of technology integration, including disparities in digital infrastructure accessibility, inadequate technological proficiency among educators, resource scarcity in underdeveloped regions, and prevailing socio-cultural apprehensions towards the assimilation of technological tools in educational environments. Nevertheless, the study also highlights promising avenues, such as the strategic adoption of the Technological Pedagogical Content Knowledge (TPACK) framework, the expansion of e-learning ecosystems and digital platforms, alongside robust governmental initiatives aimed at fostering digital transformation within the education sector. Ultimately, the findings affirm that the effective integration of technology into the 2013 Curriculum possesses substantial potential to revolutionise learning quality, contingent upon the implementation of well-crafted policies, sustained professional development for educators, and the equitable distribution of technological resources throughout Indonesia.